Spirit, Soul, and City: Shakespeare's 'Coriolanus' - Blits, Jan H. (Lexington Books, 2006)
Spirit, Soul, and City offers a new reading of Coriolanus, Shakespeare's most political play and the last of his great tragedies. Portraying the founding of the Roman republic and the life and soul of its legendary warrior, Coriolanus, the play brings to light not only the hidden working of Rome's mixed regime but the inherent tragic tensions in the soul's spirited tendency to strive to go beyond itself in order to be true to itself. Distinguished scholar Jan H. Blits provides a fresh interpretation of this rich, complex, and often perplexing play, combining meticulous detail and insightful breadth. Proceeding line-by-line through the play, this book reaches its conclusions by closely examining Shakespeare's text—his plot, characters, language, structure, allusions, puzzles, and other devices.